2001
DOI: 10.1136/bjo.85.4.403
|View full text |Cite
|
Sign up to set email alerts
|

The b-wave of the dark adapted flash electroretinogram in patients with advanced asymmetrical glaucoma and normal subjects

Abstract: Glaucomas are known to lead primarily to damage of the retinal ganglion cell layer. Whether other inner, middle, and outer retinal structures can also be involved in glaucomatous changes has been the object of interest of many studies during the last years. Among others, glaucoma induced histological horizontal cell alterations in the human retina, 1 increased glutamine uptake, 2 and increased expression of glial fibrillary acidic protein 3 in Müller cells were found. Histological studies to determine whether … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
28
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 13 publications
4
28
1
Order By: Relevance
“…We also compared the full-field ERG parameters of glaucoma patients with 25 healthy control subjects, and found significant differences in a-and b-waves implicit times and b-waves amplitudes, consistent with the findings discussed above [29,[43][44][45]. Thus, both the present and previous full-field ERG studies confirm a reduction in the retinal function in patients with glaucoma compared with controls.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…We also compared the full-field ERG parameters of glaucoma patients with 25 healthy control subjects, and found significant differences in a-and b-waves implicit times and b-waves amplitudes, consistent with the findings discussed above [29,[43][44][45]. Thus, both the present and previous full-field ERG studies confirm a reduction in the retinal function in patients with glaucoma compared with controls.…”
Section: Discussionsupporting
confidence: 93%
“…Leydhecker reported normal values even from blind eyes (he defined blind eyes as eyes in which the visual acuity Table 4 Multifocal electroretinogram recordings from area 1 (macular retina) and area 2 (perimacular retina/periphery) in patients, preoperatively and 2 and 6 months postoperatively (n=11) and age-matched controls (n=11) was reduced to counting fingers, hand movements and perception of light) [42]. Since then, several investigators have evaluated glaucoma patients using full-field ERG, with conflicting results [29,[42][43][44][45]. As opposed to Leydhecker [42], Fazio et al [29] reported significant differences between control groups and glaucoma patients in several of the full-field ERG parameters, such as photopic a-wave and scotopic b-wave implicit times, dark-adapted bright flash awave amplitudes, and a-and b-wave implicit times.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In fact, functional impediment of INL has been reported in both conditions. 7,[31][32][33] Finally, changes in cellular composition of the overlying retinal layers (extensive loss of RNFL and ganglion cells) can potentially alter light reflectivity of INL structures and therefore influence the measurement of INL thickness. Our study is also limited by relatively small sample size and cross-sectional study design.…”
Section: Discussionmentioning
confidence: 99%
“…It is generally believed that the flash electroretinograms, and specifically the b-wave amplitude, from glaucoma patients are unaVected, which is consistent with this idea. It is worthy to note, however, that recent reports have shown a reduction of a-wave amplitude 82 and a delay in b-wave implicit times 83 in the dark adapted flash electroretinograms (ERGs) from patients with advanced glaucoma. Interestingly, the b-wave amplitude of the ERG is slightly reduced with ageing 84 and glaucoma has been described as an "ageing disease."…”
Section: Figure 1 Possible Causes Of Ganglion Cell Death In Glaucomamentioning
confidence: 99%